Socio-economic benefits and challenges confronting oil palm production among indigenous rural farmers in Karonga district, Malawi - Noel Mweta; Alex Somuah Obeng; John Windie Ansah (Frontiers in Sustainable Food Systems)
This study investigated the socio-economic benefits and challenges of oil palm production among indigenous rural farmers in Karonga District, Malawi. The study adopted a mixed-methods approach, triangulating data using questionnaires, interviews, and focus group discussions. The questionnaires were administered to 477 households involved in oil palm production. Further, eight key informants were interviewed, and four focus group discussions were formed. This study, in examining oil palm production’s importance for sustaining indigenous rural farmers’ livelihoods found a multifaceted role in addressing food through cooking oil production, creating employment opportunities, and meeting other basic needs. Despite these benefits, challenges such as access to market, farm equipment, information and extension services, and credit persist, hindering production and socio-economic progress. Again, the Pearson correlation analysis between acres of land cultivated and benefits from oil palm production revealed −0.195 with a sig value of 0.000, signifying that as more acres of land farmers cultivate, benefits tend to reduce moderately. The researchers therefore recommended that the Malawi Ministry of Agriculture should collaborate with other stakeholders in the agriculture sector, including financial institutions and the manufacturing industry, in the provision of extension services as a means of information access, creating the market, and providing credits to indigenous rural farmers so that they can invest and buy equipment necessary for this agricultural activity.